Adolescent Violent Delinquency Associated With Increased Emergency Department Usage in Young Adulthood - Portnoy, Jill (International journal of offender therapy and comparative criminology, 2023)
Limited research has examined the extent to which adolescent delinquency predicts healthcare usage in young adulthood, including emergency department (ED) visits. This study used data from 3,310 adolescents (52.05% female; mean age at Wave I = 16.04 years) from the sibling subsample of the National Longitudinal Study of Adolescent to Adult Health (Add Health). We examined whether adolescent delinquency at Wave I predicted ED visits at Wave III using sibling fixed effects models to adjust estimates for within-family unobserved heterogeneity. Increased violent, but not nonviolent, delinquency predicted a higher number of ED visits in early adulthood in the sibling fixed effects models. To our knowledge, this is the first study to examine the relationship between delinquency and ED usage using a sibling fixed effects design. Findings demonstrate that violent adolescent delinquency may increase healthcare usage and suggest the potential role of healthcare providers in improving outcomes for delinquent youth.